Business law - Ellison, John.; Bedingfield, Jim.; Harrison, Tom. ([S.l.] : Business Education Publishers Ltd, 1993)
A book designed to be a guide to meeting the needs of students who are studying business law as part of an HND, degree or professional programme. The material in the text is fully up to date with frequent use of diagrammatic approaches to the study of the subject.
Keywords: business law